Fe- and Mn-modified SO42−/ZrO2 conjoined O2–Ac2O as a composite catalytic system for highly selective nitration of 1-nitronaphthalene with NO2 to valuable 1, 5-dinitronaphthalene. Issue 11 (16th September 2021) - Yan, Jiaqi; You, Kuiyi; Ni, Wenjin; Duan, Ting; Chen, Zhenpan; Zhao, Fangfang; Luo, He'an
Abstract : NO2 as benign nitrating agent and Fe–Mn bimetallic modified SZ as catalyst replaced traditional nitric–sulfuric mixed acid systems for 1-NN nitration. The synergism of Fe1.5 Mn0.5 –SZ and O2 –Ac2 O significantly improved the selectivity to 1, 5-DNN. Abstract : In the present study, a mild and efficient method for highly selective preparation of 1, 5-dinitronaphthalene from the catalytic nitration of 1-nitronaphthalene with NO2 promoted by O2 –Ac2 O over Fe- and Mn-modified SO4 2− /ZrO2 (FeMn–SZ) has been developed. The results demonstrated that 1-nitronaphthalene conversion and 1, 5-dinitronaphthalene selectivity were remarkably improved in the synergetic catalysis of Fe1.5 Mn0.5 –SZ and O2 –Ac2 O. Under optimal reaction conditions, 92.6% 1-nitronaphthalene conversion with 57.2% 1, 5-dinitronaphthalene selectivity was achieved. The characterization results unveiled that the Fe- and Mn- species of Fe1.5 Mn0.5 –SZ had been highly dispersed on the entire ZrO2 lattice, which could effectively inhibit the loss of sulfate groups and facilitate the formation of smaller crystallite sizes, resulting in higher acidity and surface area of the catalyst. The present catalyst exhibited excellent reusability and regeneration. A plausible catalytic nitration reaction mechanism was proposed. This work affords a practical and feasible new process for preparing a high proportion of 1, 5-dinitronaphthalene from the low-temperature catalytic nitration of 1-nitronaphthalene, which has potential industrial application prospects.